Randomised trial of the fascia iliaca block versus the ‘3-in-1’ block for femoral neck fractures in the emergency department - Reavley, Paul; Montgomery, Alan A.; Smith, Jason E.; Binks, Simon; Elder, Georgina; Benger, Jonathan; Edwards, Judith (BMJ Publishing Group, 2014)
Introduction: Femoral neck fractures are a common and painful injury. Femoral nerve blocks, and a variant of this technique termed the ‘3-in-1’ block, are often used in this patient group, but their effect is variable. The fascia iliaca compartment block (FIB) has been proposed as an alternative, but the relative effectiveness of the two techniques in the early stages of care is unknown. We therefore compared the FIB versus the 3-in-1 block in a randomised trial conducted in two UK emergency departments. Methods: Parallel, two-group randomised equivalence trial. Consenting patients >18 years with a femoral neck fracture were randomly allocated to receive either a FIB or a 3-in-1 block. The primary outcome was pain measured on a 100 mm visual analogue scale at 60 min. The between-group difference was adjusted for centre, age, sex, fracture type, pre-block analgesia and pre-block pain score. Results: 178 patients were randomised and 162 included in the primary analysis. The mean 100 mm visual analogue pain scale score at 60 min was 38 mm in the FIB arm and 35 mm in the 3-in-1 arm. The adjusted difference between the arms was 3 mm, with a 95% CI (−4.7 to 10.8) that excluded a clinically important difference between the two interventions. Conclusions: FIB is equivalent to the 3-in-1 block for immediate pain relief in adult neck of femur fractures.